THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, NON-PHYSICAL WORK ENVIRONMENT, AND COMPENSATION ON EMPLOYEE JOB SATISFACTION PT. PERTA ARUN GAS (PAG) LHOKSEUMAWE - Nelmi, Nelmi; Nurmala, Nurmala; Faliza, Nur (LPPM Universitas Malikussaleh, 2024)
This research was conducted to test the direct influence of Transformational Leadership, Non-Physical Work Environment, and Compensation on Employee Job Satisfaction in a company. The purpose of this research is to determine the level of job satisfaction of employees who work at PT. Perta Arun Gas (PAG) Lhokseumawe. Therefore, research was conducted using data that had been collected through direct or manual surveys with a sample size of 100 employees. To analyze the collected data, SPSS and multiple linear regression were used. The research results show that the Transformational Leadership variable has a positive and significant effect on employee job satisfaction. Meanwhile, non-physical work environment variables have no effect on employee job satisfaction. Furthermore, the compensation variable has a positive and significant effect on employee job satisfaction. These findings provide useful implications for policy makers to determine strategies related to human resource factors to increase employee job satisfaction